2022
DOI: 10.3390/su142315757
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Elements as Development Factors of Health Tourism in South Serbia

Abstract: The area of Southern Serbia is the most undeveloped tourist area and is marginalized in relation to the total tourist traffic of Serbia. With the purpose of health tourism development, special attention in this paper is focused on five spas and four mountain tourist destinations of South Serbia. The interaction of climatic elements is key for outdoor tourist activities, thus the potential of health tourism is presented through the results of the tourism climate comfort index (TCCI). According to TCCI values ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…CDMS contains magnesium above 50 mg/L, the limit for use as a dietary supplement. Since there is evidence that the bicarbonate anion also reduces cardiovascular risks (Quattrini et al, 2017) offer climatotherapy, relevant studies indicated that the annual sunshine duration should be between 1500 and 2200 hours (Stankovic et al, 2022)…”
Section: Hidrojeokimyamentioning
confidence: 99%
“…CDMS contains magnesium above 50 mg/L, the limit for use as a dietary supplement. Since there is evidence that the bicarbonate anion also reduces cardiovascular risks (Quattrini et al, 2017) offer climatotherapy, relevant studies indicated that the annual sunshine duration should be between 1500 and 2200 hours (Stankovic et al, 2022)…”
Section: Hidrojeokimyamentioning
confidence: 99%
“…Currently, the identification methods for WTAs primarily rely on qualitative research, while quantitative research is largely based on traditional statistical methods. These methods include Questionnaire Survey Method (QSM) ( 13 ), Analytic Hierarchy Process (AHP) ( 14 ), and Fuzzy Comprehensive Evaluation Method (FCEM) ( 15 ). For instance, Li and Xu ( 16 ) evaluated the construction and development potential of forest wellness bases from multiple levels using AHP and FCEM.…”
Section: Introductionmentioning
confidence: 99%